ARTIFICIAL INTELLIGENCE IN MEDICAL DIAGNOSTICS – SOCIAL AND ETHICAL IMPLICATIONS - Ignarska, Justyna; Kubicz Mzabi, Sabina; Piech, Bartosz; Judzińska, Alicja; Sobczyńska, Kamila; Terbosh, Magda; Trojanowska, Emilia; Dubaj, Magdalena; Kwolek, Marlena; Osipowska, Julia (International Journal of Innovative Technologies in Social Science, 2026)
Artificial intelligence (AI) has become one of the most transformative technologies in contemporary medicine, particularly in the field of medical diagnostics. Advanced machine learning and deep learning systems are increasingly used to analyze medical images, clinical records and complex biomedical data, offering improvements in diagnostic accuracy, efficiency and standardization of care. Alongside these technological advancements, the integration of AI into diagnostic practice generates significant social and ethical challenges that require careful examination. The objective of this review article is to critically analyze the social and ethical implications of artificial intelligence in medical diagnostics based on existing scientific literature. This article was applied, drawing on statements of some organisations, systematic reviews, policy reports and ethical analyses published between 2018 and 2026. The findings indicate that AI-driven diagnostics can enhance early disease detection. Also it can improve access to healthcare. However, they also raise concerns regarding professional accountability, algorithmic bias, transparency, data privacy, patient autonomy and healthcare equity. The review highlights the necessity of interdisciplinary governance frameworks, ethical oversight and continuous evaluation to ensure that AI technologies are implemented in a manner consistent with the core values of medicine and social justice.